Tax literacy among salaried individuals in Sarawak / Nero Madi … [et al.] - Madi, Nero; Kamaluddin, Amrizah (2003)
The focal issue under investigation comprises gauging the general level of tax literacy among different demographic groups of salaried taxpayers in Sarawak. The motivation to undertake this tax literacy study is very much prompted by the implementation of Self Assessment System (SAS) on salaried taxpayers beginning from the year 2004 where taxpayers are expected to be functionally literate to compute their own tax liabilities. This study also investigates the taxpayers' awareness on issues relevant to SAS. For the purpose of this study, samples were randomly taken from salaried taxpayers working in Kuching, Sibu, Bintulu and Miri. Statistical tests using One-Way ANOVA were applied on the mean tax literacy scores by employment sector and working experience.